RELASI ADAT DAN AKAD DALAM PRAKTIK EKONOMI SYARIAH UMKM BERBASIS BUDAYA LOKAL - Zainal Arifin (CV JK Riset Publishing Group, 2025)
This study aims to analyze the integration of Lampung's customary values with sharia contracts in UMKM economic practices in West Tulang Bawang, Metro, and Bandar Lampung. Economic ethnography method was employed involving 45 informants through in-depth interviews and participatory observation over six months. Research findings indicate that piil pesenggiri philosophy (nemui nyimah, nengah nyappur, sakai sambayan, juluk adok) converges with maqashid sharia in UMKM practices. The sakai sambayan system in West Tulang Bawang produces qardh al-hasan financing with 87% compliance rate. Murabahah contracts based on nemui nyimah in Metro increase customer loyalty up to 75%. Musyarakah partnerships with juluk adok principles in Bandar Lampung achieve 45% annual turnover growth. The study concludes that the supremacy of trust and customary-based social networks serves as an effective enforcement mechanism, yet faces modernization challenges requiring comprehensive empowerment strategies through sharia microfinance institutions, digital platforms based on local values, and certification systems for sharia economic sustainability.